2018
DOI: 10.1038/s41437-018-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving accuracies of genomic predictions for drought tolerance in maize by joint modeling of additive and dominance effects in multi-environment trials

Abstract: Breeding for drought tolerance is a challenging task that requires costly, extensive, and precise phenotyping. Genomic selection (GS) can be used to maximize selection efficiency and the genetic gains in maize (Zea mays L.) breeding programs for drought tolerance. Here, we evaluated the accuracy of genomic selection (GS) using additive (A) and additive + dominance (AD) models to predict the performance of untested maize single-cross hybrids for drought tolerance in multi-environment trials. Phenotypic data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
80
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 61 publications
10
80
1
1
Order By: Relevance
“…Our findings are also supported by goodness-of-fit values since dominance models are more parsimonious than the additive model. Accordingly, other studies have shown similar empirical results [Resende et al, 2017, Dias et al, 2018. Despite the importance of dominance effect in grain yield, additivity explained a large portion of variance in grain moisture, suggesting that both traits have different genetic architectures.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our findings are also supported by goodness-of-fit values since dominance models are more parsimonious than the additive model. Accordingly, other studies have shown similar empirical results [Resende et al, 2017, Dias et al, 2018. Despite the importance of dominance effect in grain yield, additivity explained a large portion of variance in grain moisture, suggesting that both traits have different genetic architectures.…”
Section: Discussionsupporting
confidence: 68%
“…Progress in hybrid breeding can be greatly accelerated by the incorporation of genomic predictions into breeding schemes [Technow et al, 2014, Acosta-Pech et al, 2017, Dias et al, 2018, Werner et al, 2018. To this end, breeders have to face important issues regarding its implementation, including the impact of accounting for non-additive effects and dealing with G×E interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of GS, Dias et al. () demonstrated joint modelling of additive and dominance effects for a maize MET data set. Their approach also accommodated non‐genetic sources of variation and employed a factor analytic model for both sources of VEI following Oakey et al.…”
Section: Introductionmentioning
confidence: 99%